The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1039/c1cc13904e
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of forcible curvature in circular DNA by human topoisomerase I

Abstract: A series of forcible curved circular DNAs (cDNAs) were prepared to investigate the recognition features of human Topoisomerase I (hTopo I). The IC(50) can be modulated by the curvature degrees of cDNA. In addition, preferential bindings of hTopo I to cDNA with high curvature have been observed by AFM and EMSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Further investigations revealed that when gap, nick-containing, C3-spacer-containing, and so on, were constructed into the non-supercoiled substrates, the resultant duplex structures could form covalent linkages with topoisomerase I in irreversible fashions 24–29 . In addition, certain non-supercoiled DNA was designed in our previously studies that displayed high inhibition on the activity of human topoisomerase I according to the recognise characteristic of the enzyme 30–33 . These previous studies have inspired us to speculate that the non-supercoiled oligonucleotides, if modified properly in its structure (such as introduced into a bulge structure), could serve as an inhibitor of Btopo I in the relaxation reaction of supercoiled DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations revealed that when gap, nick-containing, C3-spacer-containing, and so on, were constructed into the non-supercoiled substrates, the resultant duplex structures could form covalent linkages with topoisomerase I in irreversible fashions 24–29 . In addition, certain non-supercoiled DNA was designed in our previously studies that displayed high inhibition on the activity of human topoisomerase I according to the recognise characteristic of the enzyme 30–33 . These previous studies have inspired us to speculate that the non-supercoiled oligonucleotides, if modified properly in its structure (such as introduced into a bulge structure), could serve as an inhibitor of Btopo I in the relaxation reaction of supercoiled DNA.…”
Section: Introductionmentioning
confidence: 99%